Answer:
We conclude that:
![\sqrt{\left(-81\right)x^2}=9ix](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cleft%28-81%5Cright%29x%5E2%7D%3D9ix)
Step-by-step explanation:
Given the radical expression
![\sqrt{\left(-81\right)x^2}](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cleft%28-81%5Cright%29x%5E2%7D)
simplifying the expression
![\sqrt{\left(-81\right)x^2}](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cleft%28-81%5Cright%29x%5E2%7D)
Remove parentheses: (-a) = -a
![\sqrt{\left(-81\right)x^2}=\sqrt{-81x^2}](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cleft%28-81%5Cright%29x%5E2%7D%3D%5Csqrt%7B-81x%5E2%7D)
Apply radical rule: ![\sqrt{-a}=\sqrt{-1}\sqrt{a},\:\quad \mathrm{\:assuming\:}a\ge 0](https://tex.z-dn.net/?f=%5Csqrt%7B-a%7D%3D%5Csqrt%7B-1%7D%5Csqrt%7Ba%7D%2C%5C%3A%5Cquad%20%5Cmathrm%7B%5C%3Aassuming%5C%3A%7Da%5Cge%200)
![=\sqrt{-1}\sqrt{81x^2}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B-1%7D%5Csqrt%7B81x%5E2%7D)
Apply imaginary number rule: ![\sqrt{-1}=i](https://tex.z-dn.net/?f=%5Csqrt%7B-1%7D%3Di)
![=i\sqrt{81x^2}](https://tex.z-dn.net/?f=%3Di%5Csqrt%7B81x%5E2%7D)
Apply radical rule: ![\sqrt[n]{ab}=\sqrt[n]{a}\sqrt[n]{b},\:\quad \mathrm{\:assuming\:}a\ge 0,\:b\ge 0](https://tex.z-dn.net/?f=%5Csqrt%5Bn%5D%7Bab%7D%3D%5Csqrt%5Bn%5D%7Ba%7D%5Csqrt%5Bn%5D%7Bb%7D%2C%5C%3A%5Cquad%20%5Cmathrm%7B%5C%3Aassuming%5C%3A%7Da%5Cge%200%2C%5C%3Ab%5Cge%200)
![=\sqrt{81}i\sqrt{x^2}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B81%7Di%5Csqrt%7Bx%5E2%7D)
![=9i\sqrt{x^2}](https://tex.z-dn.net/?f=%3D9i%5Csqrt%7Bx%5E2%7D)
Apply radical rule: ![\sqrt[n]{a^n}=a,\:\quad \mathrm{\:assuming\:}a\ge 0](https://tex.z-dn.net/?f=%5Csqrt%5Bn%5D%7Ba%5En%7D%3Da%2C%5C%3A%5Cquad%20%5Cmathrm%7B%5C%3Aassuming%5C%3A%7Da%5Cge%200)
![=9ix](https://tex.z-dn.net/?f=%3D9ix)
Therefore, we conclude that:
![\sqrt{\left(-81\right)x^2}=9ix](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cleft%28-81%5Cright%29x%5E2%7D%3D9ix)
If by description you mean simplification then: 84x/28
Answer:
gosh...…. dang brainly why do you have to be like that. you were literally trying to help ppl hippo and they just shut you down like that... ugh why rude.
Step-by-step explanation:
im sorry :(
Answer:
C
Step-by-step explanation:
The last one is absurd. You can't have a ladder reaching higher than itself. The question is a Pythagorean problem.
Givens
a = 3
b = ?
c = 25 feet
Formula
a^2 + b^2 = c^2
Solution
3^2 + b^2 = 25^2
9 + b^2 = 625 Subtract 9 from both sides.
b^2 = 625 - 9
b^2 = 616 Take the square root of both sides.
b = sqrt(616)
b = 24.8